The perception ergonomic seating chair in lecture hall: student comfortability and body posture - Nor Hashim, Abdul Aziem; Mad Lazim, Halim (Universiti Utara Malaysia, 2020)
The objective of this study is to identify experience when sitting on the chair in Lecture Hall 6, to identify the knowledge about ergonomics among males and females and to determine factors likely cause the ergonomic problem. The population of this study is students from School and Technology Management and Logistics (STML). Primary data get from the questionnaire survey and observation while secondary data from articles and books. Findings for this study shown respondents have agreed they feel completely comfortable while sitting on the chair in Lecture Hall 6 and they also agreed forceful movement is the factor likely cause ergonomic effect. It is expected that students and lecturers will get more knowledge about ergonomic from this study.